2020
DOI: 10.1136/jech-2020-214217
|View full text |Cite
|
Sign up to set email alerts
|

Social and physical neighbourhood characteristics and loneliness among older adults: results from the MINDMAP project

Abstract: BackgroundLoneliness is associated with several adverse mental and physical health outcomes in older adults. Previous studies have shown that a variety of individual-level and perceived area-level characteristics are associated with loneliness. This study examined the associations of objectively measured social and physical neighbourhood characteristics with loneliness.MethodsWe used cross-sectional data from 1959 older adults (63–98 years) who participated in the Longitudinal Ageing Study Amsterdam (LASA; wav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…For example, Lee and Tan's (2019) survey in Texas reveals no association of loneliness with both objective (Walk Score) and perceived neighborhood accessibility (ease of walking to stores and transit and whether there were many places to walk to). Timmermans et al (2020), in a Dutch study, find no associations between loneliness and objectively measured land-use mix within 1 km radius around participants' homes (N = 1,956; aged 63-98 years).…”
Section: Neighborhoodsmentioning
confidence: 89%
See 1 more Smart Citation
“…For example, Lee and Tan's (2019) survey in Texas reveals no association of loneliness with both objective (Walk Score) and perceived neighborhood accessibility (ease of walking to stores and transit and whether there were many places to walk to). Timmermans et al (2020), in a Dutch study, find no associations between loneliness and objectively measured land-use mix within 1 km radius around participants' homes (N = 1,956; aged 63-98 years).…”
Section: Neighborhoodsmentioning
confidence: 89%
“…Studies that use either objective measurements or measured a single aspect are less likely to identify associations between walkability and loneliness (Finlay and Kobayashi 2018; Lee and Tan's 2019; Timmermans et al 2020;van den Berg et al 2016). For example, Lee and Tan's (2019) survey in Texas reveals no association of loneliness with both objective (Walk Score) and perceived neighborhood accessibility (ease of walking to stores and transit and whether there were many places to walk to).…”
Section: Neighborhoodsmentioning
confidence: 99%
“…For example, based on data from Hongkong, a previous cross-sectional study showed an association between higher neighbourhood social cohesion and lower loneliness levels among older adults prior to the COVID-19 pandemic [8]. In contrast, based on cross-sectional data from the Netherlands prior to the pandemic, another former study did not find an association between objectively measured social and physical neighbourhood characteristics and loneliness among older adults [9]. Former research also demonstrated an association between living in a deprived area and higher social exclusion in later life prior to the pandemic [11].…”
Section: Introductionmentioning
confidence: 93%
“…For example, these reviews showed that being married is a protective factor against loneliness and social isolation [6,7]. While several of these sociodemographic determinants of loneliness and social isolation have been clarified among middle-aged and older adults, only a few studies exist investigating the association between neighbourhood-related factors and loneliness as well as perceived social isolation [8,9,10,11,12,13]. For example, based on data from Hongkong, a previous cross-sectional study showed an association between higher neighbourhood social cohesion and lower loneliness levels among older adults prior to the COVID-19 pandemic [8].…”
Section: Introductionmentioning
confidence: 99%
“…Disadvantaged neighbourhoods also contributed to shopping difficulty [ 168 ], worse health [ 169 ], and loneliness [ 170 ]. However, there was no strong evidence that neighbourhood characteristics were associated with loneliness in another study [ 171 ]. Reduced odds of psychological distress was associated with greater employment deprivation [ 172 ].…”
Section: Resultsmentioning
confidence: 98%